ANALISIS STRATEGI PENGEMBANGAN EKOWISATA AIR TERJUN WAI POAR DALAM KAWASAN HUTAN KEMASYARAKATAN DI DESA BORU KEDANG, KECAMATAN WULANGGITANG, KABUPATEN FLORES TIMUR - Marie I. R. I. Kewuren; Ludji Michael Riwu Kaho; Wilhelmina Seran (Wana Lestari, 2019)
This study aims to determine and analyze SWOT, namely strengths, weakness, opportunities, threats as ecotourism development strategy of Wai Poar waterfall in Boru Kedang village, Wulanggitang sub-district, east Flores regency. This study was conducted in December 2018 in Boru Kedang village. Hypothesis stated is the SWOT analysis strategy in first quadrant that can improve the ecotourism development of Wai Poar waterfall. This study was a type of descriptive research of collection data for hypothesis testing and answered questions from research subject by using purposive sampling method. The population in this study was the community of Boru Kedang village. The data used are primary data and secondary data. Collection data techniques in this study were conducted through interviews, observation, distribution of questionnaires and documentation. The research method used in this study was quantitative analysis. The result of this study showed that at present, Wai Poar waterfall ecotourism has not utilized the oppurtunities that exist optimally. Therefore, the strategy that must be applied in waterfall ecotourism development is to complement the supporting infrastructure of private activities, such as: roads, cleaning facilities, etc., create policy that are specific to ecotourism development, synergize ecotourism with the arts and culture, empower local communities in ecotourism activities.